Mengoptimalkan Pengelolaan Keuangan dengan RKT, RKA, RAPB - Siti Rosyidatul Umma; Mardiyah Mardiyah (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Effective financial management is a crucial aspect in ensuring the sustainability and growth of an organization, including in the context of social and profit organizations (SOPI). The Revenue and Expenditure Budget Plan (RAPB) is the main instrument in financial management, which not only functions as a guideline for allocating resources, but also as a strategic tool in achieving organizational goals. This study uses a library research method to explore how systematic budget planning can improve financial efficiency and ensure transparent and accountable use of funds. This study highlights the importance of preparing formal documents such as annual work plans, budget work plans, and RAPB in ensuring that organizations can manage resources in a more structured and measurable manner. By applying analysis to various literature sources, this study identifies steps in preparing an effective RAPB, including revenue estimation, expenditure allocation, and budget evaluation and control mechanisms. The results of the study show that a well-prepared RAPB can help organizations set priorities, measure performance, and avoid waste of resources. In addition, RAPB also acts as an internal communication tool that clarifies the direction and goals of the organization to all stakeholders. With a strict evaluation system, organizations can ensure that the budget used has an optimal impact on achieving the vision and mission that have been set.